A proposed energy efficient medium access control protocol for wireless sensor networks - Al-Rikabi, Yasser Kareem Hummadi (2014)
Wireless Sensor Network (WSN) nodes are broadly used in various sectors nowadays. WSN nodes experience a lot of problems that impact on battery life for sensor node such as, overhearing, collision, hidden node, idle listening, schedule drifts, and high latency. Moreover, WSN nodes are strongly dependent on its limited battery power, and replenishing it again is difficult as nodes are organized in an ad-hoc manner. Energy consumption is the most vital factor to determine the life of a sensor network because sensor nodes are driven by low battery resources. An approach to conserve energy in WSN nodes is to carefully design its Medium Access Control (MAC) protocol. Several previous work has been carried out to mitigate many problems that impact on battery life for sensor node such as overhearing, collision, and hidden node. This dissertation attempts to design, a hybrid Energy-Efficient MAC (EEMAC) protocol to address the energy issues that are related to WSN nodes. This protocol aims to reduce idle listening times as well as lowering the latency time thus reducing the energy consumption. The proposed protocol has been developed and analysed using the ns-2 simulator. A mathematical model was used to verify and prove the efficiency of the proposed protocol. We have compared our proposed EE-MAC protocol with the existing contention-based IEEE 802.11 PSM protocol. The simulation results illustrate EE-MAC has achieved better energy conservation than the IEEE 802.11 PSM protocol.